Characterization for identification of selected Philippine varieties of Adlay (Coix lacryma-jobi L.) and evaluation for food source - YUMUL, RAQUEL (Archīum Ateneo, 2017)
The study seeks to establish if Pulot and Tapol varieties exhibit variations by detailed characterization of their seed morphology, physical traits, physicochemical properties, cooking and eating properties, antioxidant properties, post-harvest trait and physiological traits. Scanning electron microscopy, spectrophotometry, measuring length, width and height, cooking, and seed germination were the major procedures employed. Descriptive analysis was applied for the physical characteristics of adlay grains. Pulot and Tapol varieties were compared based on standard deviation or median for normal and non-normal data, respectively. Shapiro-Wilk's, Independent samples t-test, Two-way analysis of variance and Mann-Whitney test were carried out and 5% level of significance was considered. Data set was analyzed using StataIC 13. Seed coat pattern of Pulot and Tapol is simple reticulate. Their starch granules shape is round, polygonal and grain shape that is circular. Appearance of furrow is also evident on grains. Size of starch granule in Pulot is larger than Tapol. The seed weight and husk/seed weight ratio of Pulot and Tapol are the same. Pulot variety has heavier seeds, longer grain and seeds and wider grain and seeds than that of Tapol. Protein and amylose are the same for Pulot and Tapol. The swelling power and solubility of both varieties are low. Pulot and Tapol have a low phenolic content and high reducing power. Gelatinization temperature for both varieties is high and their seeds form soft gels after cooking. Seed moisture content between the two cultivars is the same. Pulot and Tapol seedlings are the same in standard germination test (SG), cold test (CT), but different in accelerated aging test (AT). Stronger seedlings developed under SG and CT in Pulot variety. Length of seedlings and roots are the same under SG and CT. Results for size of starch granules of Pulot and Tapol can be used in describing starch functionality especially in food production. Seed weight, grain and seed length, grain and seed width distinguished the physical character of Pulot from Tapol. Both varieties contain high amount of protein which can supply essential amino acids in the body. Very amount of amylose and reducing power in both cultivars should be tested again to confirm its results. Amount of antioxidant present in Pulot and Tapol poses possibility in the prevention degenerative diseases. Low swelling power and solubility of Pulot and Tapol is an indication of more water requirement during cooking. Gelatinization temperature is high which indicates a longer time for cooking the grains of both varieties and they form soft grains after cooking. Pulot germinates more seeds and its seedlings are viable as compared to Tapol.